Higher Physical Activity Levels May Help Buffer the Negative Psychological Consequences of Coronavirus Disease 2019 Pandemic - Antunes, Raul; Rebelo-Gonçalves, Ricardo; Amaro, Nuno; Salvador, Rogério; Matos, Rui; Morouço, Pedro; Frontini, Roberta (Frontiers in Psychology, 2021)
This study explored the associations between subjective measures of physical activity (PA), assessed by the IPAQ questionnaire, anxiety levels, and the perception of satisfaction of basic psychological needs (BPN), during COVID-19 lockdown. Thus, 1404 participants (977 women,426 men and one respondent preferred not to answer) (36.4±11.7 years-old) over 18 years-old, ranging from 18-89 years old (36.4±11.7 years-old) completed a questionnaire in the period between 1st-15th MarchApril, 2021. The survey included sociodemographic data and the following validated instruments: the International Physical Activity Questionnaire (IPAQ), the Basic Need General Satisfaction Scale and the State-Trait Anxiety Inventory. The Kruskal-Wallis test was performed to examine variation in anxiety levels and BPN satisfaction according to PA category (low, moderate and high). The association between anxiety levels and psychological needs was also computedSpearman's Rho correlations coefficients were used to determine the association between anxiety levels and psychological needs. Individuals presenting a higher level of PA revealed lower levels of anxiety-state (H=20.14; p=<0.01). Differences between elements from different levels of PA were found for the autonomy (H=23.52; p=<0.001), competence (H=18.89; p=<0.001) and relatedness (H=24.42; p=<0.001) psychological needs, suggesting that those who feel their BPN as more satisfied have higher levels of PA. The study found statistically significant correlations between anxiety-state and the satisfaction of the needs for autonomy (p=0.01; r=-0.46), competence (p=0.01; r=-0.40), and relatedness (p=0.01; r=-0.21). These findings support the importance that PA has in the anxiety levels during social isolation, emphasizing the importance of multidisciplinary teams in an individual-based approach.